ANALYSIS OF THERAPEUTIC TREATMENT EFFECTIVENESS OF CAT URINARY BLADDER STONE DISEASE - Burtseva, D. D.; Lokes-Krupka, T. P.; Kravchenko, S. O.; Khomenko, A. N. (Scientific Progress & Innovations, 2021)
The paper analyzes the statistical data on the incidence of cat urolithiasis. The study was conducted during the period of 2020–2021. The objects of clinical and laboratory studies were 40 domestic cats of different age groups, sexes and breeds, which during a comprehensive study had a pronounced clinic of urolithiasis. Analyzing the spreading of urolithiasis among cats, we took into account gender, age, breed, type of feeding, seasonality, the type of stones, their localization in the urinary tract, recurrence and causes of the disease. According to our research, urolithiasis was registered most often in uncastrated cats aged from 4 to 6 years, less frequently in cats under one year of age and over 10. When diagnosing urolithiasis, we were guided by the results of clinical and laboratory studies. From clinical indicators, we took into account the general condition, behavior, body temperature, pulse, respiratory rate, condition of the mucous membranes, the results of the kidneys and bladder palpation; the symptoms noticed by the owners were also considered. The information on the initial manifestations of the disease, the duration and urination disorders were important. Through the collection of anamnesis, we obtained the information about the conditions of keeping, the diet structure and feed quality. The main diagnostic criteria were clinical manifestations – dysuria, colic, weakness, forced posture; urine laboratory indicators – proteinuria, hemoglobinuria, excessive amounts of oxalates, erythrocytes and leukocytes in the sediment, as well as the epithelium of the urinary bladder. Urolith of increased echogenicity and sand in the urinary bladder were detected by ultrasonography. The treatment of domestic cats’ urolithiasis includes a complex set of treatment and prevention procedures. The conservative treatment, depending on the disease stage and symptoms, takes a long time; it is conducted before surgery and after it. We have developed a scheme for the treatment of domestic cats suffering from urinary bladder stone disease. It included: Katazal, NoSpa, Dexafort, Meloxicam, Etamzilate and Sinulox. The treatment effectiveness is indicated by the improvement of the animals’ clinical condition and the normalization of urine indicators.